Evolution of life cycles and reproductive traits: Insights from the brown algae. (23rd June 2021) - Heesch, Svenja; Serrano‐Serrano, Martha; Barrera‐Redondo, Josué; Luthringer, Rémy; Peters, Akira F.; Destombe, Christophe; Cock, J. Mark; Valero, Myriam; Roze, Denis; Salamin, Nicolas; Coelho, Susana M.
Abstract: A vast diversity of types of life cycles exists in nature, and several theories have been advanced to explain how this diversity has evolved and how each type of life cycle is retained over evolutionary time. Here, we exploited the diversity of life cycles and reproductive traits of the brown algae (Phaeophyceae) to test several hypotheses on the evolution of life cycles. We investigated the evolutionary dynamics of four life‐history traits: life cycle, sexual system, level of gamete dimorphism and gamete parthenogenetic capacity. We assigned states to up to 77 representative species of the taxonomic diversity of the brown algal group, in a multi‐gene phylogeny. We used maximum likelihood and Bayesian analyses of correlated evolution, while taking the phylogeny into account, to test for correlations between traits and to investigate the chronological sequence of trait acquisition. Our analyses are consistent with the prediction that diploid growth evolves when sexual reproduction is preferred over asexual reproduction, possibly because it allows the complementation of deleterious mutations. We also found that haploid sex determination is ancestral in relation to diploid sex determination. However, our results could not address whether increased zygotic and diploid growth are associated with increased sexual dimorphism. Our analyses suggest that in the brown algae, isogamous species evolved from anisogamous ancestors, contrary to the commonly reported pattern where evolution proceeds from isogamy to anisogamy. Abstract : The brown algae are a eukaryotic lineage that evolved complex life cycles independently of plants and animals, with several instances of haploid‐dominant, diploid‐dominant and equally dominant life cycles. We reconstructed the history of life cycle evolution throughout the brown algae alongside other reproductive traits, such as the sex‐determination system, the gamete sizes and the ability to undergo parthenogenesis. We also performed correlation analyses between the evolutionary transitions of these traits to test several long‐standing hypotheses concerning the evolution of life cycles in eukaryotes.